Strategies to Reduce the Cost of Medical Education in India: A Narrative Review - Shrivastava, Saurabh R.; Shrivastava, Prateek S. (Avicenna Journal of Medicine, 2022)
Background The global population is being plagued by several diseases and health conditions, and this calls for the need to adopt a strategy to enable people from all socioeconomic backgrounds to have the freedom and choice to opt for a medical profession as their career. The purpose of the current review is to explore the reasons which make medical education expensive and identify the strategies by which the cost of medical education can be minimized.Methods An extensive search of all materials related to the topic was performed on the PubMed search engine and web site of the National Medical Commission. Relevant research articles focusing on costs in medical education published in the period 2005 to 2021 were included in the review. A total of 37 articles were selected based on their suitability with the current review objectives and analyzed. Keywords used in the search include medical education and cost in the title alone only.Results We have to accept the fact that medical education is quite expensive and that's not the case with one nation but the trend is worldwide. It is the need of the hour to plan and implement strategies that make medical training accessible and available to people from all socioeconomic classes and regardless of other variables.Conclusion In conclusion, the process of training medical students is expensive and accounts for a wide range of impacts on the medical aspirants. Thus, there is an indispensable need for the policy makers and the concerned stakeholders to join their hands together and take appropriate steps to minimize the overall cost of medical training, and thereby making it affordable to everyone.
Keywords: cost; government; medical education; India; accreditation; technology; community